The Dynamic Link between Electricity Production, Financial Development, Trade Openness and Economic Growth: The Evidence from Lao PDR - Bouapao, Leesert (International Journal of Multidisciplinary in Management and Tourism, 2020)
The purpose of this paper is to examine the causality between electricity production, financial development, trade openness and economic growth in Lao PDR during 1984 to 2015. We use the bounds test and auto- regressive distributed lag (ARDL) for approaching to co-integration in the long-run, the vector error correction model (VECM) for testing the direction of causality among the series. The results of the paper showed that there is co-integrated between electricity production, financial development, trade openness and economic growth. Moreover, there is bi-directional causality between electricity and economic growth in the long run, and we found uni-directional causality running from financial development and trade openness inelectricity production and economic growth. The policy implication of this result is that development strategies should prioritize on financial development and trade openness, and this study also supports the view of government to invest in electricity generation which will promote economic growth in the long term.